Mammary alveolar epithelial cells convert to brown adipocytes in post‐lactating mice. Issue 11 (24th March 2017) - Giordano, Antonio; Perugini, Jessica; Kristensen, David M.; Sartini, Loris; Frontini, Andrea; Kajimura, Shingo; Kristiansen, Karsten; Cinti, Saverio
Abstract : During pregnancy and lactation, subcutaneous white adipocytes in the mouse mammary gland transdifferentiate reversibly to milk‐secreting epithelial cells. In this study, we demonstrate by transmission electron microscopy that in the post‐lactating mammary gland interscapular multilocular adipocytes found close to the mammary alveoli contain milk protein granules. Use of the Cre‐loxP recombination system allowed showing that the involuting mammary gland of whey acidic protein‐Cre/R26R mice, whose secretory alveolar cells express the lacZ gene during pregnancy, contains some X‐Gal‐stained and uncoupling protein 1‐positive interscapular multilocular adipocytes. These data suggest that during mammary gland involution some milk‐secreting epithelial cells in the anterior subcutaneous depot may transdifferentiate to brown adipocytes, highlighting a hitherto unappreciated feature of mouse adipose organ plasticity. Abstract : In this study, we demonstrate by transmission electron microscopy that in the post‐lactating mammary gland interscapular multilocular adipocytes found close to the mammary alveoli contain milk protein granules. Use of the Cre‐loxP recombination system allowed showing that the involuting mammary gland of whey acidic protein‐Cre/R26R mice, whose secretory alveolar cells express the lacZ gene during pregnancy, contains some X‐Gal‐stained and uncoupling protein 1‐positive interscapular multilocular adipocytes. These data suggest that during mammary gland involution some milk‐secreting epithelial cells in the anterior subcutaneous depot may transdifferentiate to brown adipocytes.